Pengaruh Media Big Book Terhadap Kemampuan Menyimak Anak Usia 5-6 Tahun di TK Pembina HKBP Tarutung - Sofania Magdalena Siadari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of big books on the listening skills of 5-6 year old children at the Pembina HKBP Tarutung Kindergarten. The research hypothesis was: